Synthesis of enantiopure non-natural α-amino acids using tert-butyl (2S)-2-[bis- (tert-butoxycarbonyl)amino]5-oxopentanoate as key-intermediate: The first synthesis of (S)-2-amino-oleic acid - Constantinou-Kokotou, V.; Magrioti, V.; Markidis, T.; Kokotos, G. (Journal of Peptide Research, 2001)
A general method for the synthesis of enantiopure non-natural α-amino acids is described. The key intermediate tert-butyl (2S)-2-[bis(tert-butoxycarbonyl)amino]-5-oxopentanoate was obtained from l-glutamic acid after suitable protection and selective reduction of the γ-methyl ester group by DIBALH. Wittig reaction of this chiral aldehyde with various ylides led to a variety of δ,ε-unsaturated α-amino acids. This methodology was applied to the synthesis of (S)-2-amino-oleic acid.